Tinjauan Literatur Transformasi Sosial dalam Era Virtual - Aan Setiadarma; Ahmad Zaki Abdullah; Priyono Sadjijo; Dwi Firmansyah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Social transformation in the virtual era has become an increasingly relevant research subject with the expanding penetration of digital technology in human life. Recent literature studies reveal various aspects related to virtual sociology, including the formation of online communities, the role of technology in identity formation, and the impact of social media on culture and public opinion. This research aims to compile a comprehensive literature review on social transformation in the virtual era, identifying current trends, important findings, and recent developments in virtual sociology studies. Additionally, this study aims to investigate the social impacts arising from changes in social interaction and culture in the digital world. Employing a comprehensive literature review approach, this research gathers and evaluates various relevant literary sources, including journal articles, books, research reports, and other information sources related to social transformation in the virtual era. The findings of this research provide a deeper understanding of social dynamics in the virtual era, including the formation of online communities, digital identity, and the role of social media in shaping public opinion. The information obtained from this literature review can serve as a reference for researchers, practitioners, and policymakers in addressing challenges and opportunities arising from social changes driven by digital technology. The social transformation in the virtual era plays a significant role in shaping the dynamics of modern society. Studies on virtual sociology offer valuable insights into how digital technology influences human behavior, interaction, and social structures in the virtual world.